Adjuvant Pertuzumab and Trastuzumab in Early HER2-Positive Breast Cancer in the APHINITY Trial: 6 Years' Follow-Up. Issue 13 (1st May 2021) - Piccart, Martine; Procter, Marion; Fumagalli, Debora; de Azambuja, Evandro; Clark, Emma; Ewer, Michael S.; Restuccia, Eleonora; Jerusalem, Guy; Dent, Susan; Reaby, Linda; Bonnefoi, Hervé; Krop, Ian; et al.
Abstract : PURPOSE: APHINITY, at 45 months median follow-up, showed that pertuzumab added to adjuvant trastuzumab and chemotherapy significantly improved invasive disease–free survival (IDFS) (hazard ratio 0.81 [95% CI, 0.66 to 1.00], P = .045) for patients with early human epidermal growth factor receptor 2 (HER2)–positive breast cancer (BC), specifically those with node-positive or hormone receptor (HR)–negative disease. We now report the preplanned second interim overall survival (OS) and descriptive updated IDFS analysis with 74 months median follow-up. METHODS: After surgery and central HER2-positive confirmation, 4, 805 patients with node-positive or high-risk node-negative BC were randomly assigned (1:1) to either 1-year pertuzumab or placebo added to standard adjuvant chemotherapy and 1-year trastuzumab. RESULTS: This interim OS analysis comparing pertuzumab versus placebo did not reach the P = .0012 level required for statistical significance ( P = .17, hazard ratio 0.85). Six-year OS were 95% versus 94% with 125 deaths (5.2%) versus 147 (6.1%), respectively. IDFS analysis based on 508 events (intent-to-treat population) showed a hazard ratio of 0.76 (95% CI, 0.64 to 0.91) and 6-year IDFS of 91% and 88% for pertuzumab and placebo groups, respectively. The node-positive cohort continues to derive clear IDFS benefit from pertuzumab (hazard ratio 0.72 [95% CI, 0.59 to 0.87]), 6-year IDFS being 88% and 83%, respectively. Benefit was not seen in the node-negative cohort. In a subset analysis, IDFS benefit from pertuzumab showed a hazard ratio of 0.73 (95% CI, 0.59 to 0.92) for HR-positive disease and a hazard ratio of 0.83 (95% CI, 0.63 to 1.10) for HR-negative disease. Primary cardiac events remain < 1% in both the treatment groups. No new safety signals were seen. CONCLUSION: This analysis confirms the IDFS benefit from adding pertuzumab to standard adjuvant therapy for patients with node-positive HER2-positive early BC. Longer follow-up is needed to fully assess OS benefit.